Micro Financing Mechanism with Murobahah Agreement At BSI KCP Probolinggo Kraksaan - Salimatul Imaniah (IJED: International Journal of Economy Development Research, 2024)
Bank Syariah Indonesia (BSI) Probolinggo Kraksaan is a financial institusion in the from of a non-public bank using Sharia principes in its operations, standing in a strategic location near the main road that is easy to reach for the public, and has a vision and mission that can advance it.the research aims to the micro financing mechanism with a murabahah contract at Bank Syariah Indonesia (BSI), to find out the obstacles faced in the micro financing mechanism with a murabahah contract at Bank Syariah Indonesia (BSI). This type of research uses qualitative. The objec of research examined is the mechanism of micro financing with murabahah contacts cerried out at KCP BSI Kraksaan. The data analysis method uses descriptive qualitative Micro financing with a murabahah contract at Bank Syariah Indonesia (BSI) Kraksaan has 9 stages and most of them are based on theory from the OJK Shariabanking product standard book (2116). The stages that are not in accordance with the theory carriedout by bank are the stages of collecting customer data and rations.